Acousto-microfluidics for screening of ssDNA aptamer - Park, Jee-Woong (Sci Rep, 2016)
We demonstrate a new screening method for obtaining a prostate-specific antigen (PSA) binding aptamer based on an acoustofluidic separation (acoustophoreis) technique. Since acoustophoresis provides simultaneous washing and separation in a continuous flow mode, we efficiently obtained a PSA binding aptamer that shows high affinity without any additional washing step, which is necessary in other screening methods. In addition, next-generation sequencing (NGS) was applied to accelerate the identification of the screened ssDNA pool, improving the selecting process of the aptamer candidate based on the frequency ranking of the sequences. After the 8(th) round of the acoustophoretic systematic evolution of ligands by exponential enrichment (SELEX) and following sequence analysis with NGS, 7 PSA binding ssDNA aptamer-candidates were obtained and characterized with surface plasmon resonance (SPR) for affinity and specificity. As a result of the new SELEX method with PSA as the model target protein, the best PSA binding aptamer showed specific binding to PSA with a dissociation constant (K(d)) of 0.7 nM.